1992
DOI: 10.1346/ccmn.1992.0400203
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Polysaccharides with Silver Hill Illite

Abstract: Abstract--The clay-polysaccharide interaction is of practical importance in the formation and stabilization of soil aggregates. This study examined the adsorption of three synthetic polysaccharides (PSS) and one soil PSS on Silver Hill illite. The adsorption of PSS was influenced by both the adsorbed cations on the adsorbents and the charge characteristics of the polymers. The adsorbed cations formed different surface complexes with the clay surfaces, with varying ability to screen the surface negative charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…While other studies have demonstrated that purified soil constituents can adsorb and potentially affect the subsequent degradation of chemicals, most of these studies have not been performed under typical soil solution conditions with intact soil communities. Commonly, the adsorption and desorption of chemicals is examined in dilute solutions of the soil constituent, which do not represent the typical soil solutions or soil water activity (a,) (6,12,31,38,39,41). The unique value of this study is that mineralization of chemicals in known environmental forms was measured under realistic aw conditions, at which the biological, chemical, and physical characteristics of a natural soil were largely preserved.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have demonstrated that purified soil constituents can adsorb and potentially affect the subsequent degradation of chemicals, most of these studies have not been performed under typical soil solution conditions with intact soil communities. Commonly, the adsorption and desorption of chemicals is examined in dilute solutions of the soil constituent, which do not represent the typical soil solutions or soil water activity (a,) (6,12,31,38,39,41). The unique value of this study is that mineralization of chemicals in known environmental forms was measured under realistic aw conditions, at which the biological, chemical, and physical characteristics of a natural soil were largely preserved.…”
Section: Discussionmentioning
confidence: 99%
“…The humic acid (HA) sample was isolated from a local soil (Gu and Doner, 1992). It was purified with a mixture of 0.1 M HCI and 0.1 M HF,…”
Section: Methodsmentioning
confidence: 99%
“…This can take place either directly or through a water bridge (Gu and Doner, 1992). Given the affinity of alginate for calcium ions and the previously described 'egg-box' crosslinking mechanism, it is likely that the presence of Ca 2+ ions could help to create electrostatic bridges between the anionic part of the polymer and the clay surface (Yalçın et al, 2002).…”
Section: Alginate As An Additive For Unfired Masonrymentioning
confidence: 99%